Qualidade de vida de pais de crianças e adolescentes com transtorno do espectro autista : um estudo na Paraíba - Duarte, Gabriela Nóbrega (2025)
INTRODUCTION: The diagnosis of autism spectrum disorder (ASD) entails changes in family dynamics and can lead to emotional and psychosocial impacts, such as frustration, fear, grief, and emotional overload. The quality of life of parents and caregivers of autistic children is affected by the physical, emotional, and social demands of daily care, often resulting in overload, mental health issues, and fatigue. The quality of life of parents and caregivers of children and adolescents diagnosed with ASD is an increasingly relevant topic in the field of health and family well-being, given the physical, emotional, and social demands that permeate the daily care of this population. Studies highlight the importance of understanding these challenges to ensure equitable access to healthcare, education, and support services, fostering a more inclusive future for these families. OBJECTIVE: To assess the quality of life of parents of children and adolescents diagnosed with ASD in the state of Paraíba, Brazil. METHODS: This is a cross-sectional, observational, exploratory, and analytical study, conducted online and targeting parents and caregivers in the state of Paraíba between September and November 2024. The data collection instrument was administered via Google Forms. For data collection, sociodemographic information was considered, using instruments for sociodemographic characterization and assessment of QVTEA (Quality of Life of Caregivers of Children and Adolescents with Autism Spectrum Disorder). Data were analyzed using R software (RStudio version 2024.12.0 Build 467©, 2009–2024 Posit Software, PBC). The results were examined through descriptive and inferential statistics, as well as the development of a Binary Logistic Regression Model to determine the factors that best explain quality-of-life outcomes. RESULTS: The study sample consisted of 95 participants, with 91.58% female and 8.42% male. Participants' ages ranged from 23 to 49 years (M = 35.5; SD = 6.06). Regarding educational level, 49.47% had higher education, while 50.53% had other levels of schooling. Most participants resided in metropolitan areas (51.04%), and 57.9% had two or more children. In terms of support levels, 31% required level 1 support, 47% level 2, and 18% level 3. The mean quality of life scores (QVTEA) was 20.4 (SD = 4.81) for physical health, 22.4 (SD = 5.21) for social aspects, 20.1 (SD = 5.05) for psychological health, and 17.5 (SD = 5.02) for concerns. The total mean score was 82 (SD = 16.18). Univariate analysis revealed statistically significant associations between quality of life and sex (p = 0.005), indicating that men reported better quality of life. Additionally, there was a marginally significant association with educational level (p = 0.05), suggesting that participants with higher education had better scores. Comparative analysis showed that higher quality of life was associated with higher scores in physical health (p < 0.01), social aspects (p < 0.01), psychological health (p < 0.01), and lower levels of concern (p < 0.01). Logistic regression indicated that working in operational services (OR = 0.26; p = 0.03), being in the "Other" job category (OR = 0.22; p = 0.01), and requiring level 3 support (OR = 0.24; p = 0.01) were factors negatively influencing quality of life. CONCLUSION: The results show that sociodemographic and occupational factors and the level of support required by the child or adolescent influence caregivers' quality of life. These findings reinforce the need for policies and interventions that provide adequate support, aiming to reduce caregiver burden and improve the well-being of these families.